2016
DOI: 10.1590/1806-9061-2016-0242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fermented Garlic on the Growth Performance, Relative Organ Weights, Intestinal Morphology, Cecal Microflora and Serum Characteristics of Broiler Chickens

Abstract: The present study was conducted to evaluate the effects of feeding broilers with garlic fermented by Leuconostoc citreum SK2556. A total of 250 male broiler chicks was randomly housed into 25 floor pens. Five dietary treatments with five replicates of 10 chicks each (n=50 chicks/ treatment). A corn and soybean meal based diet was used as the control diet (NC). The experimental diets were formulated by mixing the basal diet either with antibiotics (10 ppm; PC) or fermented garlic (FG) at the concentrations of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
4
9
0
1
Order By: Relevance
“…Moreover, the increase of OE in diets linearly decreased CD. This is in agreement with other studies of broiler chickens, that have shown reduced jejunal CD in birds fed with garlic extract compared to a control [48]. According to these authors, a reduced CD suggests a lower turnover rate to maintain VH and, hence, lower energy needs to maintain gut integrity.…”
Section: Effect Of Olive Pomace Extractsupporting
confidence: 92%
“…Moreover, the increase of OE in diets linearly decreased CD. This is in agreement with other studies of broiler chickens, that have shown reduced jejunal CD in birds fed with garlic extract compared to a control [48]. According to these authors, a reduced CD suggests a lower turnover rate to maintain VH and, hence, lower energy needs to maintain gut integrity.…”
Section: Effect Of Olive Pomace Extractsupporting
confidence: 92%
“…Fermentation is commonly used in southeast Asian countries (South Korea, China, and Japan) for the preservation of foodstuffs and to increase nutritional value . Lactobacillus buchneri , Bacillus subtilis , and Bacillus licheniformis are widely used for feed fermentation and have been applied with beneficial effects in feed for broilers . Seaweeds and seaweed extracts have been used to feed livestock for a long time, and the beneficial effects on broilers include improving growth performance and immune status and altering the microflora in the digestive tract .…”
Section: Discussionmentioning
confidence: 99%
“…Each plate was incubated at 37°C, for 24 to 72 h and colonies were then counted. Results obtained were presented as base-10 logarithm colony-forming units per gram of cecal digesta [ 16 ].…”
Section: Methodsmentioning
confidence: 99%